Quality Expectations and Willingness to Pay of German, Italian, and Turkish Strawberry Consumers - Özeltürkay, Eda Yaşa; Predieri, Stefano; Medoro, Chiara; Gatti, Edoardo; Cianciabella, Marta; Daniele, Giulia Maria; Mazzoni, Luca; Karhu, Saila; Latvala, Terhi; Kafkas, Ebru; Sönmez, Duygu Ayvaz; Olbricht, Klaus; et al. (MDPI, 2026)
This study investigated consumer expectations and perceived quality of strawberries across different geographical contexts to identify the main drivers of purchasing behavior within a cross-country framework. An online survey was conducted among consumers in Italy, Germany, and Turkey to explore consumption habits, purchasing channels, sensory expectations, product perceptions, and willingness to pay (WTP) for specific product attributes. Results confirmed a high level of consumer appreciation for strawberries across all countries, primarily driven by their sensory characteristics. However, purchasing behavior and consumption patterns were strongly influenced by cultural and market-related factors. Visual attributes were confirmed to be key cues guiding product choice; however, label indications related to sensory traits and functional properties exerted a greater influence. Flavor, firmness, and overall taste balance represented critical determinants of consumer satisfaction. Differences across demographic groups were also observed, with younger and male consumers reporting lower levels of satisfaction with key sensory attributes, including juiciness, aroma, and freshness. Cross-country comparisons revealed heterogeneous WTP patterns, with Turkish consumers showing a greater propensity to pay premium prices for quality-related, local, organic, and environmentally friendly attributes compared with German and Italian consumers. Overall, the findings highlight the combined influence of sensory quality, cultural context, and sociodemographic characteristics in shaping strawberry perception and purchasing behavior. These insights may support breeders, producers, and retailers in developing targeted product strategies and market positioning across different geographical areas and consumer segments.
Keywords: strawberry; consumer experience; quality assessments; quality expectations; WTP